Towards a smoke-free world? South America became the first 100% smoke-free subregion in the Americas - Gianella Severini; Rosa Carolina Sandoval; Gustavo Sóñora; Patricia Sosa; Patricia Gutkowski; Luciana Severini; Víctor Valdivia; Ernesto M. Sebrié (Pan American Health Organization, 2022)
Almost 20 years after the launching by the Pan American Health Organization of its "Smoke-Free Americas" initiative in 2001, in December 2020, South America became the first subregion in the Americas to accomplish 100% smoke-free environments in line with Article 8 of the World Health Organization Framework Convention on Tobacco Control (FCTC). Some of these countries adopted legal measures that are more robust than others, including in their laws specific outdoor places in the smoking ban (like Argentina and Uruguay) and/or novel nicotine and tobacco products under their scope (like Ecuador and Paraguay). The 10 countries took different paths to adopt this public health measure, either through executive or legislative measures or a combination of both. A few countries, like Argentina, Brazil, and Venezuela, started at the subnational level and then moved on to the national level, similar to the rest of the countries. For achieving this milestone, an adequate context was crucial: the broad ratification of the FCTC and the relevance given to the human right to health, civil society efforts, commitments made by intergovernmental bodies, media and communication strategies, and the development of scientific evidence. Countries faced obstacles, including the well-known interference of the tobacco industry, which among other strategies used litigation; however, courts and judges upheld comprehensive legal measures on smoke-free environments. The process by which South America achieved this milestone represents a role model for other subregions of the Americas and the world.